2018
DOI: 10.1136/vr.104440
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of feline urinary tract pathogens and antimicrobial resistance over five years

Abstract: The aim of this retrospective study was to document the prevalence of bacterial species in cats with significant bacteriuria and to compare their antimicrobial susceptibilities over five years. One hundred sixty-nine positive urine cultures from 150 cats were included. Fifty-five per cent showed clinical signs, while 40 per cent had subclinical bacteriuria. , species, species, species and accounted for 50.5 per cent, 22.9 per cent, 15,1 per cent, 3.6 per cent and 2.6 per cent, respectively. species was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
3
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 44 publications
7
52
3
6
Order By: Relevance
“…The most commonly identified staphylococcal species among isolates from both the stray cats and hospitaladmitted cats was S. felis; this is in accordance with a previous German study, which showed that half of the Staphylococcus spp. isolates obtained were S. felis, but inconsistent with the results of studies in USA and South Africa, which have shown that S. intermedius/ pseudintermedius and S. epidermidis were the representative staphylococci present in cats [19][20][21]. S. felis has been regarded as a normal commensal organism present on the skin, the conjunctival sac and eyelid margins, and in the saliva of normal healthy cats, as well as an etiological agent that causes skin infections such as pyoderma and otitis [22,23].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The most commonly identified staphylococcal species among isolates from both the stray cats and hospitaladmitted cats was S. felis; this is in accordance with a previous German study, which showed that half of the Staphylococcus spp. isolates obtained were S. felis, but inconsistent with the results of studies in USA and South Africa, which have shown that S. intermedius/ pseudintermedius and S. epidermidis were the representative staphylococci present in cats [19][20][21]. S. felis has been regarded as a normal commensal organism present on the skin, the conjunctival sac and eyelid margins, and in the saliva of normal healthy cats, as well as an etiological agent that causes skin infections such as pyoderma and otitis [22,23].…”
Section: Discussioncontrasting
confidence: 95%
“…isolates, the most prevalent species was E. faecalis, followed by E. faecium; this is in accordance with a German study, which showed that E. faecalis represented the vast majority of the Enterococcus spp. isolates (26 of 29 isolates) [21]. No Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly identified staphylococcal species among isolates from both the stray cats and hospital-visiting cats was S. felis; this is in accordance with a previous German study, which showed that half of the Staphylococcus spp. isolates obtained were S. felis, but inconsistent with the results of studies in USA and South Africa, which have shown that S. (pseud)intermedius and S. epidermidis were the representative staphylococci present in cats [27][28][29]. S. felis has been regarded as a normal commensal organism present on the skin, the conjunctival sac and eyelid margins, and in the saliva of normal healthy cats, as well as an etiological agent that causes skin infections such as pyoderma and otitis [30,31].…”
Section: Discussioncontrasting
confidence: 95%
“…isolates, the most prevalent species was E. faecalis, followed by E. faecium; this is in accordance with a German study, which showed that E. faecalis represented the vast majority of the Enterococcus spp. isolates (26 of 29 isolates) [29]. No Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies of hyperthyroid cats have reported a prevalence of UTI ranging from 12 to 22%, 5,6 and consisting mostly of subclinical bacteriuria. Consequently, clinicians consider hyperthyroidism a risk factor for development of UTI, 3,7 and many recommend urine culture as a part of the routine evaluation of hyperthyroid cats 8,9 …”
Section: Introductionmentioning
confidence: 99%